SMART TECHNOLOGY OPPORTUNITIES IN LEARNING ENGLISH: SMART TECHNOLOGY OPPORTUNITIES IN LEARNING ENGLISH - Tajieva, Aliya (Журнал иностранных языков и лингвистики, 2025)
When we say about smart technology we mean digital tools and systems which consist of advanced computing power, connectivity, and interactive capabilities to improve activities in different spheres, including education. In the contemporary era, which is characterized by the prevalence of global connections, the capacity to engage in cross-cultural interactions is becoming an increasingly crucial skill. [1; 214] In today’s education system we have opportunities to use smart technologies like artificial intelligence (AI), mobile applications, and other technologies like virtual reality (VR) and augmented reality (AR).